Assessment of the Service Life of Reinforced Concrete and Steel Elements - Mirzaahmedov Oʻgʻiloy Abduxalimjonovna; Toshmatov Ulugʻbek Qodirjon oʻgʻli (Zien Journals, 2022)
The article provides information on the service life of metal and reinforced concrete elements,their shelf life, assessment of the technical condition of damaged elements to increase their strength
Keywords: corrosion protection of structures; steel reinforcement; degree of carbonization of concrete; durability of reinforced concrete structures